2016
DOI: 10.1097/mpg.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical, Endoscopic, and Pathological Features of Duodenitis in Children

Abstract: Objectives While gastritis and esophagitis are well studied in children, there is very limited literature on duodenitis in children. We aimed to assess the prevalence, etiology, clinical, endoscopic, and pathological features in a large cohort of unselected children with duodenitis. Methods We reviewed the pathology reports of all upper endoscopies performed at our institution over 5 years to identify children with duodenitis. Biopsy sections were reviewed to confirm the diagnosis of duodenitis. Demographic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 11 publications
3
30
0
4
Order By: Relevance
“…Alper et al[34] reported that duodenitis is identified in 12.7% of children undergoing endoscopy with celiac disease and IBD as the most common etiologies. The prevalence of duodenitis in childhood CD and UC ranges from 33%-48% and 0%-29%, respectively[13,35-37].…”
Section: Duodenal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alper et al[34] reported that duodenitis is identified in 12.7% of children undergoing endoscopy with celiac disease and IBD as the most common etiologies. The prevalence of duodenitis in childhood CD and UC ranges from 33%-48% and 0%-29%, respectively[13,35-37].…”
Section: Duodenal Inflammationmentioning
confidence: 99%
“…The prevalence of duodenitis in childhood CD and UC ranges from 33%-48% and 0%-29%, respectively[13,35-37]. More than half of children with biopsy-proven duodenitis demonstrate unremarkable duodenal mucosa on endoscopy[34]. Macroscopic abnormalities associated with duodenitis include edema, erythema, erosions, scalloping, and ulcers[34].…”
Section: Duodenal Inflammationmentioning
confidence: 99%
“…Long et al[ 18 ] reported a sensitivity of 54% and specificity of 92% for prediction of duodenal histology by macroscopic findings in pediatric biopsy-proven duodenitis. A recent article investigated duodenitis in children with multiple gastrointestinal diagnoses, including CD, and found a sensitivity of 34% for endoscopic diagnosis in predicting duodenal histology[ 19 ]. Lastly, Sheiko et al[ 20 ] reported the correlation of macroscopic and histologic findings in 1000 pediatric patients with a variety of gastrointestinal concerns, 6.6% of who had histology consistent with celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CGD associated with Helicobacter pylori (H. pylori) infection varies according to the age of the child, being 20% in children aged 4-9 years, 40% in children aged between 10-14 years, and 52-70% in children over 15 years and adults [10][11][12][13] . The prevalence of FA among children ranges from 12.0 to 37.0%, which is significantly higher than in adults [14][15][16][17] . Most researchers emphasize the only mechanism of the occurrence of this pathology -the immunoallergic one 18-20. Morphologically, such patients have allergic reactions in the mucous membranes and skin 21 .…”
Section: Introductionmentioning
confidence: 95%